Perspectives and Movement of Nadlatul Ulama (NU) in Counter-Terrorism - Chairul Huda, Muhammad; Yusriyadi , Yusriyadi; Thohir, Mudjahirin (International Journal of Psychosocial Rehabilitation, 2020)
Nahdlatul Ulama (NU), as part of international law subjects in the form of non-governmental organizations (NGOs), has a commitment to participate in maintaining world peace. The purpose of the NU movement is on the values of Islamic universality (maqasidus sharia). This research used a qualitative method with a post-positivism paradigm. The results of this study are NU since its establishment in 1926 until the present era, NU has always been consistently conducting anti-radicalism and counter-terrorism movements both through the study of religious interpretations as a method of thought (manhajul fikr), through education in the style of the salaf pesantren (traditional Islamic boarding school) and the counter-terrorism movement in virtual space (social media). NU has teaching character that is in line with the values of Islamic universality (maqasidus Sharia); those are tawazun (balanced) and tasamuh (tolerant) in the frame of ukhuwah islamiyah (brotherhood of fellow Muslims), ukhuwah wathoniyah (brotherhood of fellow citizens) and ukhuwah insaniyah (brotherhood of fellow human beings) towards peaceful human civilization and Islam, which is a blessing for the universe (rahmatan lil alamin).